Old Testament’s Notes for a Systematic Theology of Expiation - Medina Balguerías, Marta (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2021)
To help to clarify the concept of «expiation» this article seeks to trace its main elements in the Old Testament’s theology. After an overview of the uses of the term in the Old Testament we focus on the expiation in the priestly document (where it is understood in the context of ritual sacrifices) and then on its intercessory dimension, with a special focus on the mediation of the Deuteroisaiah’s servant of Yahweh. We conclude that expiation is a relational process in which God removes evil from the human being and enables reconciliation (with the person’s participation and normally with a mediator).